Racial and Ethnic Disparities in Cardio-Oncology: A Call to Action - Fazal, Muhammad (JACC CardioOncol, 2021)
• Racial or ethnic health care disparities in cardio-oncology are present, although data remain sparse. • These disparities stem from structural racism, higher prevalence of CVD risk factors, and reduced access to specialty care. • A multidisciplinary approach is required to dismantle these disparities and should include key stakeholders, including health care policy makers, patients, scientists, and clinicians.